Carotid endarterectomy without protective measures in patients with occluded and non occluded contralateral carotid artery - Dimakakos, P.B.; Antoniou, A.; Papasava, M.; Mourikis, D.; Rizos, D. (Journal of Cardiovascular Surgery, 1999)
Background. Comparison of carotid endarterectomy in patients with and without occluded contralateral carotid artery. Methods. Design: evaluation of results without using shunt or patch. Setting: Aretaeion Hospital, Medical School, University of Athens. Subjects: 235 patients, divided into group I of 40 patients with and group II of 195 patients without occluded contralateral carotid artery. Intervention: carotid endarterectomy under general anesthesia. Main outcome measures: heparin administration, stable hemodynamic status during clamping, short duration monitoring postoperatively. Results. Postoperative morbidity of both groups was 2.5 (6/235) and mortality 1.7 (4/235). Group I: mortality rate was 2.5 (1/40) major and minor stroke each 2.5 (1/40) and group II: 1.5 (3/195) and 1 (2/195) respectively (NS). Four to 108 months later, 30 (12/40) of group I and 21 (41/195) of group II died. Conclusions. Endarterectomy of the carotid artery under general anesthesia without use of shunt and patch in patients with or without occlusion of the contralateral carotid artery presented the same comparative results. Candidates for carotid endarterectomy should be screened systematically for coronary disease preoperatively and annual stress testing postoperatively, tactics which may improve early and late mortality rate after carotid surgery.
Keywords: Carotid artery diseases surgery; Carotid stenosis; Cerebral ischemia; Endarterectomy, carotid